Prevalence and risk behaviors of Opisthorchis viverrini reinfection of people in Sisaket Province - namwong, Worawut; Songserm, Nopparat; Bureelerd, Onanong (UBRU Journal for Public Health Research, 2019)
Clonorchis sinensis and Opisthorchis viverrini are still public health problems in East Asia and Southeast Asia. Thailand is one of the areas where many patients with Opisthorchis viverrini infection are found, especially in the Northeast. Most importantly, Opisthorchis viverrini infection is the main cause of cholangiocarcinoma. Opisthorchis viverrini reinfection increases the risk of cholangiocarcinoma. The study of prevalence and risk behaviors of Opisthorchis viverrini reinfection, therefore, is important for assessing the situation of the spread of the disease and recognizing the causes of the risk behaviors of Opisthorchis viverrini infection in the area. The results of this study can also be used in the planning of public health operations. This was a cross-sectional study which aimed to study the prevalence and the risk behaviors of Opisthorchis viverrini reinfection of people in Sisaket Province. The samples were selected by multi-stage sampling method. They were 68 people in the responsibility area of Thung Chai Health Promoting Hospital and Hua Chang Health Promoting Hospital, Uthumphon Phisai District, Sisaket Province. All of them had been detected with liver fluke eggs in the stool, confirmed by the public health authorities using the Kato’s Thick Smear. The data were collected by the questionnaire on risk behaviors of Opisthorchis viverrini reinfection of people in Sisaket Province. Descriptive statistics, including frequency, percentage, mean and standard deviation were employed for data analysis. The research revealed that the samples’ rate of Opisthorchis viverrini reinfection was 16.18%. The results of the risk behaviors of Opisthorchis viverrini reinfection showed that the score of practices of most of the samples was at a moderate level, accounted for 45.59%. The risk behaviors of Opisthorchis viverrini reinfection of the samples included eating papaya salad with uncooked fermented fish sauce, eating chili paste with uncooked fermented fish sauce and eating uncooked or half-cooked Plasom (soured fermented fish). However, the behavior of defecation outside the toilet was not much found.